The Blues Greats - Muddy Waters Memphis Slim (USA Passport International, 2004)
The names McKinley Morganfield and Peter Chapman might not ring many bells, but when you call them Muddy Waters and Memphis Slim and add one more name - Willie Dixon, you get a trio of veteran bluesmen who paved the way for such major rock 'n' roll bands of the Sixties and Seventies as The Beatles and The Rolling Stones. The Blues Greats lets you hear and see Muddy, Memphis, and Willie at their very best, along with fellow blues giants Amos Milburn, Matt ""Guitar"" Murphy, Lonnie Johnson, Victoria Spivey, Sonny Boy Williamson, and the great Big Joe Williams. It's a kickin' collection no blues fan should be without!
With Muddy Waters, Willie Dixon, and Memphis Slim leading the way, this group of veteran bluesman show us why their music had such a major impact on the rock n' roll bands of the 60's and 70's, including The Beatles and The Rolling Stones.
Pat Britt
Language: English
Subtitle: "No Subtitle"
Keywords: Music